How to build a thriving fee-for-service practice : integrating the healing side with the business side of psychotherapy - Kolt, Laurie (Practical resources for the mental health professional., 1999)
Twenty years ago, a therapist could hang up a shingle, make some networking calls, and begin to create a steady stream of referrals. Since then, private practice has changed dramatically. Now therapists everywhere are struggling just to keep their practices going. The need has never been greater for sound business tools for building and marketing a therapy practice. How to Build a Thriving Fee-for-Service Practice is essential reading for newly licensed therapists, seasoned professionals, and others wanting to prepare practitioners for success. How to Build a Thriving Fee-for-Service Practice.